Design methodology for a combined FMCW and pulse Doppler radar front-end - Pulutan, Doreena Karmina A. (2013)
FMCW and pulse Doppler (PD) radars possess distinct characteristics that are optimized to provide specific measurements for varying applications. For example, the FMCW radar does not suffer from blind range and speed measurements. A PD radar, on the other hand, can reach long range due to its inherent clutter suppression capabilities that allow it to transmit at high power. Being able to take advantage of the features of both modes in a single radar platform leads to flexibility. In this work, we study the design of a combined FMCW and PD radar front-end. In order to do this, we first study the definitions of radar parameters and their inter-dependencies. Furthermore, a combined front-end implies weighing the trade-offs between radar performance parameters for both modes. Through cascade analysis, we determine the overall RF specifications that will allow us to utilize the advantage of each mode. System-level simulation is used to evaluate the overall specifications of the dual-mode front-end and give us an insight of how leakage plagues the FMCW radar. From there, we can identify the maximum range of the FMCW mode, and use that as starting point for the operation in PD mode. This work emphasized the trade-offs and outlined a procedure for the design of a combined FMCW and PD radar front-end. Out results show that by designing the FMCW mode with high receiver gain, we are able to achieve good sensitivity even at low transmit power. Designing the PD mode for large receiver dynamic range utilizes its ability to reach long range by transmitting at high peak and average power.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Doppler radar -- Design and construction; Frequency-modulated continuous-wave (FM-CW) radar; Pulse doppler radar